2006
DOI: 10.1080/09640560500507884
|View full text |Cite
|
Sign up to set email alerts
|

The opportunity cost of regulating phosphorus from broiler production in the Illinois River Basin

Abstract: The Illinois River Basin in eastern Oklahoma and northwest Arkansas is an example of a region where significant growth in poultry production has been accompanied by water quality problems. The primary concern in the basin is the problem of phosphorus in runoff that is associated with application of litter to crops. Existing data suggest that there has been a continuing decline in the quality of water in the Illinois River, and discussions have focused on developing and implementing a phosphorus standard. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…There is also direct evidence. About 5 % of P experimentally applied to land as litter runs off each year (Sauer et al 2000, Schroeder et al 2004, Willett et al 2006, accounting for about 71 % of Tenkiller's annual loading. Most of the P in the IR comes from litter disposal and subsequent runoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also direct evidence. About 5 % of P experimentally applied to land as litter runs off each year (Sauer et al 2000, Schroeder et al 2004, Willett et al 2006, accounting for about 71 % of Tenkiller's annual loading. Most of the P in the IR comes from litter disposal and subsequent runoff.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus losses from poultry litter-amended pastures range from 2-11 % of applied, and about 80-90 % is dissolved reactive P (Edwards and Daniel 1993, Sauer et al 1999, Schroeder et al 2004, Willett et al 2006. A conservative value of 5 % for P loss to surface water from litter-amended soils was chosen to estimate P lost to water in the IRW.…”
Section: P Loadingmentioning
confidence: 99%
“…Weidhaas et al [48,49] used a quantitative PCR assay approach to confirm that poultry waste applied in the IRW was running off and reaching streams and rivers. Willett et al [50] modeled the IRW and assumed that 5% of poultry waste that was land applied was lost to the IRW waters. Sharpley et al [30] indicated that 5% of P in poultry waste that is land applied to fields runs off, and thus may eventually reach the lake.…”
Section: Phosphorus Deliverymentioning
confidence: 99%
“…The model developed here is static and could be improved by incorporating dynamic soil nutrient effects and the value of important micronutrients such as calcium. More sophisticated means of estimating the amount of litter produced based on bird weight derived from a biological response function could also be incorporated (Willet et al, 2006). Another limitation of the study is the treatment of poultry litter as a perfect substitute for commercial fertilizers.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%